2006
DOI: 10.1302/0301-620x.88b9.17829
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of aneurysmal bone cysts with percutaneous sclerotherapy using polidocanol

Abstract: Aneurysmal bone cyst is a rare tumour-like lesion which develops during growth. Our aim was to determine the efficacy of the administration of percutaneous intralesional 3% polidocanol (hydroxypolyaethoxydodecan) as sclerotherapy. Between July 1997 and December 2004 we treated 72 patients (46 males, 26 females) with a histologically-proven diagnosis of aneurysmal bone cyst, at various skeletal sites using this method. The sclerotherapy was performed under fluoroscopic guidance and general anaesthesia or sedati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
163
3
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(192 citation statements)
references
References 32 publications
7
163
3
7
Order By: Relevance
“…The 5% recurrence rate demonstrated in this series, particularly with juxtaphyseal lesions, provides an acceptable comparative recurrence rate [1,11,16,17,25,28,33,35,36,42,44] with which to pursue further study of this percutaneous treatment option. Furthermore, when recurrence (evidence of residual foci of tumor cells) occurs, patients are able to pursue a minimally invasive option of percutaneous treatment of small recurrent foci.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…The 5% recurrence rate demonstrated in this series, particularly with juxtaphyseal lesions, provides an acceptable comparative recurrence rate [1,11,16,17,25,28,33,35,36,42,44] with which to pursue further study of this percutaneous treatment option. Furthermore, when recurrence (evidence of residual foci of tumor cells) occurs, patients are able to pursue a minimally invasive option of percutaneous treatment of small recurrent foci.…”
Section: Resultsmentioning
confidence: 82%
“…In addition, evidence of new bone healing provides key information for the physicians involved that treatment was progressing in the proper direction. Evidence of healing in 100% of patients compares favorably with surgical and nonsurgical care series [1,11,16,17,25,28,33,35,36,42,44].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a review of 72 patients with a mean follow-up of 34 months, Rastogi et al found a clinical response of 84.5 % with an average of three injections per patient [54]. In a randomized trial, Varshney et al compared polidocanol sclerotherapy with curettage, high-speed burr, and bone graft: polidocanol had a healing rate of 93.3 % compared with 84.8 % for curettage, although this difference did not reach statistical significance [50].…”
Section: Sclerotherapymentioning
confidence: 99%
“…Sclerosants, in general, act by direct damage to the endothelial lining, triggering a coagulation cascade and thrombotic occlusion of blood vessels. 11 There are earlier reports of spontaneous remission of ABC in the literature. 20 Response to autogenous bone marrow injection is also reported.…”
Section: Aneurysmal Bone Cystmentioning
confidence: 98%